Skrbimo za druge, kaj pa zase? - Videmšek, Petra (Socialno delo, 2024)
The development of self-care is shown, why is this case necessary in the field of social care, and what are the practices used by professional workers in social work for taking care of themselves. The findings of the research showed that professional workers care more for people with personal experiences of distress than for themselves. Very little time, or almost none, is dedicated to them, for their well-being and health. Based on the results of the research, a model of self-care is presented that should be introduced into the daily practice of social care. It is based on the assumption that self-care is not only the responsibility of the individual professional worker, but of the entire team and especially the organization. Self-care is necessary for the ethical implementation of social work.
Keywords: delovno okolje; dobro počutje; odpornost; resilience; self care; skrb zase; supervision; supervizija; well-being; work environment